IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PENANGGULANGAN PENGANGGURAN DI KABUPATEN KEPULAUAN SULA PROVINSI MALUKU UTARA (Suatu Studi Di Kabupaten Kepulauan Sula) - SAPSUHA, IKBAL; LONDA, VERY; PALAR, NOVIE ANDERS (Sam Ratulangi University, 2017)
ABSTRACT : The employment issue in the Sula Islands District has now reached an appreciable conditionmarked by large unemployment and underemployment, relatively low and uneven incomes, on the contraryunemployment and high unemployment are a waste of human resources and potential, the burden of familyand society, the main source of poverty, can encourage increased social and criminal unrest, and canhamper development in the long run, the future development of the Indonesian nation.Low unemployment rates can reflect good economic growth, and can reflect improvements in the quality ofthe livelihoods of the population and increased equity of income, hence the welfare of the population maythen increase. Based on the description on the background above, the authors are interested in conductingresearch with the title